2009
DOI: 10.2753/eee0012-8775470603
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Model of the Exchange Rate Pass-Through Effect

Abstract: This paper investigates the exchange rate pass-through (ERPT) effect in Croatia using a threshold model. To date, empirical studies have failed to find a high degree of ERPT in Croatia, even though exchange rate stability has been one of the goals of monetary policy throughout the transition period. Using a nonlinear model, this study demonstrates that ERPT is present in the data and shows why it cannot be detected with a linear model. According to our estimates, there is a threshold at 5.91 percent of the mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The main objectives of our research are the assessment of the influence of macro factors and the degree of the ERPT on aggregate and disaggregated import prices of industrial sectors in the short-and long-run, i.e., to examine how the degree of the ERPT affects the import prices and the composition of imports by industry and whether the degree of the ERPT is higher with homogeneous products or heterogeneous products. Nevertheless, our research differs, compared with previous empirical research related to Croatia, because they mainly focus on the estimation of the exchange rate regime to degree of ERPT (Darvas, 2001;Billmeier & Bonato, 2002;Tica & Posedel, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…The main objectives of our research are the assessment of the influence of macro factors and the degree of the ERPT on aggregate and disaggregated import prices of industrial sectors in the short-and long-run, i.e., to examine how the degree of the ERPT affects the import prices and the composition of imports by industry and whether the degree of the ERPT is higher with homogeneous products or heterogeneous products. Nevertheless, our research differs, compared with previous empirical research related to Croatia, because they mainly focus on the estimation of the exchange rate regime to degree of ERPT (Darvas, 2001;Billmeier & Bonato, 2002;Tica & Posedel, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, they found that the size eff ect is more signifi cant than the direction eff ect. Tica and Posedel (2009) showed that the EPRT is asymmetric around a particular threshold value, and the EPRT eff ect is strong and signifi cant above the threshold, but the EPRT is weak in Croatia below the threshold. Alvarez et al (2012) found a complete and non-declining pass-through to import prices but weak evidence of asymmetric pass-through from appreciation vs. depreciation in both the short run and long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The presumed inability to model the primary FX rate time series because of its non-stationarity, non-normality, heteroscedasticity, and the presence of frequent structural breaks in the time series has motivated several other authors to model the FX returns instead, and to pursue various ARCH (Autoregressive Conditional Heteroscedasticity), TAR (Threshold Autoregression) and VAR (Vector Autoregression) approaches (Posedel 2006, Tica and Posedel 2009, Erjavec et al 2012. Earlier exchange rate -inflation pass-through research did not come to converging results regarding the endogeneity of the exchange and inflation rate (Choudhri and Hakura 2001, Cukierman, Miller, and Neyapti 2002, Devereux and Engel 2003, Gagnon and Ihrig 2004, Mihaljek and Klau 2008.…”
Section: Literature Reviewmentioning
confidence: 99%